PENGARUH LEVERAGE TERHADAP TAX AVOIDANCE DENGAN BOARD DIVERSITY SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI) - Muhammad Rizal; Eny Suprapti; Sri Wahjuni Latifah (Universitas Gajayana Malang, 2018)
Abstrac: The purpose of this study was to determine the effect of Leverage on Tax Avoidance with Board Diversity as moderating variables. This research is associative research. The population in this study is a mining company listed on the Indonesia Stock Exchange. The number of samples from this study were 17 companies. Sampling was done using purposive sampling method. The method of analysis carried out in this study was the test of moderated regression analysis (MRA), classical assumption test, and partial test (t test). The results showed that the leverage had a significant effect on tax avoidance. Partially, the leverage has a significant positive effect on tax avoidance, and the board diversity moderates the relationship between the leverage and tax avoidance. Keywords: Tax Avoidance, leverage, board diversity